The impact of land use and land cover changes on land surface temperature in a rapidly urbanizing megacity - Dewan, Ashraf; Corner, Robert (IEEE, 2012)
This paper investigates the relationship between land use / land cover in the capital of Bangladesh, Dhaka. Significant differences were noted between the mean surface temperatures between land cover types. In addition the rapid urbanization of the megacity has been mapped, with the urban area expanding by 67% since 1990.